Digitizing Zakat Distribution in Malaysia: A Case Study on Application Process at Kedah State Zakat Board - Nor, Shifa Mohd; Yaacob, Salmy Edawati; Rahman, Aisyah Abdul; Zainal, Hafizah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
This research examines the implementation of the digital zakat application process for eligible recipients via the